Thermal and thermoelectric properties of ceramics based on zinc oxide alloyed with iron - Pashkevich, Aliaksei V.; Bliznyuk, Ludmila A.; Fedotov, Alexander K.; Khovaylo, Vladimir V.; Kharchanka, Andrei A.; Fedotova, Vera V. (Journal of the Belarusian State University. Physics, 2022)
In this work, we study the effect of adding iron oxides FeO and Fe2O3 in a ratio of 1 : 9 on the thermal and thermoelectric characteristics of ceramics based on zinc oxide ZnO. The samples themselves were made in two stages based on the ceramic technology of sintering powder mixtures in an open atmosphere. Thermal conductivity studies point to the dominant contribution of lattice thermal conductivity at room temperature. The decrease in thermal conductivity as a result of alloying is due to an increase in phonon scattering at point defects introduced into the ZnO lattice (due to the replacement of zinc ions by iron ions) and at grain boundaries (due to microstructure refinement), as well as an increase in porosity (a decrease in density) and the formation of particles of an additional ZnFe2O4 ferrite phase. Alloying wit iron and the accompanying change in the structure of ceramics (decrease in grain size, increase in porosity, precipitation of the ferrite phase) leads to an increase in the thermoelectric figure of merit ZT by 2 times (due to a decrease in electricalresistivity and thermal conductivity with a relatively small decrease in the thermoelectric coefficient). The results obtained can be used to fabricate ZnO-based ceramics with optimal thermoelectric characteristics.
Keywords: ceramics; zinc oxide; density; thermal conductivity; phonon scattering; thermoelectric figure of merit